Philosophy Across the Ages - Jacobson, Kirsten (Maine Policy Review, 2015)
This article describes an outreach program called Philosophy Across the Ages (PAA). PAA connects a University of Maine philosophy professor and her undergraduate students with Orono High School students through exciting biweekly seminar-style discussions of philosophical texts from ancient to contemporary times.
Keywords: humanities; philosophy; education; outreach